Empowering vegetable growers for livelihood and nutritional security - Singh, Neeraj; Roy, Shubhadeep; Rai, A. B.; Singh, P. M.; Prasad, R. N.; Singh, B. (Indian Horticulture, 2019)
Concerted vegetable research efforts in the country and the emergence of corporate sector in the vegetable seed business have contributed immensely in enhancing vegetable productivity and production. However, the growth of vegetables across the country is uneven, with 1 state in the productivity range of 25-30 tonnes/ha, 4 states in the range of 20-25 tonnes/ha, 7 states in the range of 15-20 tonnes/ha, 11 states in the range of 10-15 tonnes/ha and 6 states with less than 10 tonnes/ha vegetable productivity. In the last couple of years, ICAR-Indian Institute of Vegetable Research, Varanasi with its developed technologies significantly contributed in narrowing this gap between the potential and average national productivity by empowering vegetable growers, especially in different parts of UP, Bihar, Jharkhand, MP and Chhattisgarh through capacity building, demonstrations, quality seed availability, advisory service and various ICTs tools. As a result, the growers of these regions could realize 23.5 to 53.7% gain in productivity with 44.8-72.8% increase in net returns with different vegetable crops enabling them to achieve their objectives.